Major broiler diseases in Some parts of Haryana - MAHAJAN, N K; JINDAL, N; KULSHRESHTHA, R C (The Indian Journal of Animal Sciences, 2013)
The present study is based on postmortem and other laboratory examinations of 5 664 broiler birds along with complete history of their flocks from January 1987 to December 1990. Morbidity rate varied between 8.2 and 10.8% whereas mortality rate increased from 4.8% in 1987 to 7.6% in 1990. Major causes of mortality were E. coli infections (266 outbreaks) followed by fowl typhoid (198), coccidiosis (183), brooder's pneumonia (80), vitam n deficiency (78), CRD (73), Ranikhet disease (17) and othermiscellaneous diseases (284). Maximum mortality (10.54%) was because of fowl typhoid followed by E. coli infections (8.88%) and CRD (7.94%). The incidence of diseases was more in monsoon and winter than in summer.